Pulsed light treatment as an alternative technology to extend shelf life of fresh-cut yardlong bean (Vigna unguiculata) - Hambali, Nor Hasni; Mohd Adzahan, Noranizan; Karim, Roselina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Pulsed light (PL) treatment is a non-thermal method for microbial decontamination on the surfaces of fresh-cut produce. The effect of pulsed light fluencies on microbiological stability and quality changes of fresh-cut yardlong beans were determined. Pulsed light treatments were carried out using an automatic laboratory flash lamp system (Steribeam XeMaticA-2L Kehl, Germany) at different fluencies (1.8 J/cm2, 5.4 J/cm2, 9.0 J/cm2 and 12.6 J/cm2). Microbiological quality (colour changes and textural changes) of fresh-cut yardlong beans stored at 4±1°C were monitored over 14 days. Results show that, the application of PL treatment at high fluencies allowed extension of microbiological shelf life up to 3-7 days in comparison to untreated samples. Apart from that, PL treated sample has no significant difference on the texture and colour as compared to untreated sample of fresh-cut yardlong bean. As a conclusion, the application of PL at dose 9.0 J/cm2 has increased the shelf life of fresh-cut yardlong bean while maintaining the quality when stored at 4±1°C.